Analysis of Tourism Development Management in Increasing Regional Economic Competitiveness (Case Study: Pandeglang District, Banten) - Fia Birtha Al Sabet; Pungki Ari Wibowo (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The variety of tourism potential in Pandeglang Regency is one of the mainstays for regional economic growth and development. Natural conditions dominated by mountains and the longest beach in Banten Province make Pandeglang Regency a very promising tourism alternative. However, the various tourism potentials have not been properly mapped and optimally managed, so that a comprehensive development management is needed. The purpose of this study was to develop a management strategy for tourism development in Pandeglang Regency in increasing regional economic competitiveness. The research method used is the mixed method, namely quantitative and qualitative methods are used together to obtain comprehensive, valid, reliable and objective results. Based on the results of the analysis, Pandeglang Regency is included in a fast-growing or potential area (based on the Klassen typology) and its inequality index is said to be quite high (Williamson Index> 0.7). An alternative tourism management strategy that can be carried out by the Pandeglang Regency Government based on a SWOT analysis isare (1) increasing accessibility and building public infrastructure, public facilities, and tourism facilities, (2) improving the quality of human resources and tourism management institutions, and (3) increasing promotion by utilizing various social media.